Nasopharyngeal colonization with Streptococcus pneumoniae triggers dendritic cell dependent antibody responses against invasive disease in mice. Issue 3 (1st February 2017) - Dommaschk, Anne; Ding, Nadine; Tort Tarres, Meritxell; Bittersohl, Lara F.; Maus, Regina; Stolper, Jennifer; Jonigk, Danny; Braubach, Peter; Lippmann, Torsten; Welte, Tobias; Maus, Ulrich A.
Abstract : In the current study, we show that dendritic cells (DCs) contribute to pneumococcal colonization induced antibody responses in mice. Depletion of DCs in mice colonized with S . pneumoniae (Spn) attenuates antipneumococcal antibody responses resulting in poor protection against invasive pneumococcal disease (IPD). Abstract : Nasopharyngeal colonization with Streptococcus pneumoniae (Spn) is an important precondition for the development of pneumococcal pneumonia. At the same time, nasopharyngeal colonization with Spn has been shown to mount adaptive immune responses against Spn in mice and humans. Cellular responses of the nasopharyngeal compartment, including the nasal‐associated lymphoid tissue, to pneumococcal colonization and their importance for developing adaptive immune responses are poorly defined. We show that nasopharyngeal colonization with S. pneumoniae led to substantial expansion of dendritic cells (DCs) both in nasopharyngeal tissue and nasal‐associated lymphoid tissue of mice. Depletion of DCs achieved by either diphtheria toxin (DT) treatment of chimeric zDC +/DTR mice, or by use of FMS‐like tyrosine kinase 3 ligand (Flt3L) KO mice exhibiting congenitally reduced DC pool sizes, significantly diminished antibody responses after colonization with Spn, along with impaired protective immunity against invasive pneumococcal disease. Collectively, the data show that classical DCs contribute to pneumococcal colonization induced adaptive immune responses against invasive pneumococcal disease in two different mouse models. These data may be useful for future nasopharyngeal vaccination strategies against pneumococcal diseases in humans.